DEVELOPMENT OF DIGITAL ECONOMY IN UZBEKISTAN (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Subsequently, consistent measures are being taken to develop the digital economy, and electronic commerce systems are being gradually introduced in state bodies and other organizations for the exchange of electronic documents and the provision of services to individuals and legal entities.